Impact of early gut microbiota on immune and metabolic development and function. Issue 6 (December 2016) - Wang, Mei; Monaco, Marcia H.; Donovan, Sharon M.
Summary: Microbial colonization of the infant intestine occurs in the first two years of life. Symbiotic host and microbe interactions are critical for host metabolic and immune development. Emerging evidence indicates that early microbiota colonization may influence the occurrence of metabolic and immune diseases. Further understanding of the importance of environmental factors, including fetal microbial exposure, diet, delivery mode, pre- and probiotic consumption, and antibiotic use on immune and metabolic programming will provide new opportunities for the development of therapeutic and prophylactic measures to improve infant health and reduce the risk of disease in post-infancy years.